Engineering Microbes to Bio-Upcycle Polyethylene Terephthalate - Dissanayake, Lakshika; Jayakody, Lahiru N. (Frontiers in Bioengineering and Biotechnology, 2021)
Polyethylene terephthalate (PET) is globally the largest produced aromatic polyester with an annual production exceeding 50 million metric tons. PET can be mechanically and chemically recycled; however, the extra costs in recycling are not justified when converting PET back to the original polymer, which leads to less than 30% of PET produced annually to be recycled. Hence, waste PET massively contributes to plastic pollution and damaging the terrestrial and aquatic ecosystems. The global energy and environmental concerns with PET highlight a clear need for technologies in PET “upcycling,” a creation of a higher-value product(s) from reclaimed PET. Several microbes that degrade PET and corresponding PET hydrolase enzymes have been successfully identified. The characterization and engineering of these enzymes to selectively depolymerize PET into original monomers such as terephthalic acid and ethylene glycol has been successful. Synthetic microbiology and metabolic engineering approaches enable the development of efficient microbial cell factories to convert PET-derived monomers into value-added products. In this mini-review, we present the recent progress of engineering microbes to produce higher-value chemical building blocks from waste PET using a wholly biological and a hybrid chemocatalytic-biological strategy. We also highlight the potent metabolic pathways to bio-upcycle PET into high-value biotransformed molecules. The new synthetic microbes will help establish the circular materials economy, alleviate the adverse energy and environmental impacts of PET, and provide market incentives for PET reclamation.